Research survey of pragmatic and communicative functions in language units (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Despite the importance of the pragmatic aspect studying still little attention is paid to communicative pragmatic functions of speech and speech units. This article deals with the present day researching of pragmatic communicative functions and language units. Modern linguistics distinguishes three main approaches of classifying pragmatic (communicative pragmatic) functions. Investigating both communicative aspects of the language and pragmatic studying develops our knowledge about speaker’s language capabilities.Communicative and pragmatic investigating actually focuses on both communicative and pragmatic components of speech events. These elements enhance information about the opportunities of transferring communicatively significant meanings in the process of speaking. Unlike pragmalinguistics methods communicative and pragmatic approach gives the first priority to communicative units and puts them in the focus of studying.Communicative and pragmatic research gives a lift to better understanding of communication itself. Language is considered to be a special sort of activity aimed to various information exchange which is used to achieve non-verbal and communication targets of social life and interpersonal interaction. Pragmatic and communicative language studying applies the terms and definitions of communicative linguistics and pragmatics.Communicative and pragmatic function is one of the most important concepts in linguistic pragmatics. Observing its definition reveals the absence of unanimity of scientists’ views. Nowadays there are three main approaches in its interpretation such as communicative linguistic and linguistic pragmatic. We stick to a common linguistic interpretation of pragmatic communicative functions as a means to influence the behavior and consciousness of people in the process of communication. On assumption of already mentioned facts all pragmatic functions of speech contribute to the realization of communicative and pragmatic intentions in texts. There is a certain interconnection between the pragmatic purpose of expressions and communicative pragmatic functions.
Keywords: communicative pragmatic functions of speech; speech unit; speech event; language unit; communicative linguistics; pragmatics